Colloidal gold‐McAb probe‐based rapid immunoassay strip for simultaneous detection of fumonisins in maize. (27th October 2016) - Yao, Jingjing; Sun, Yaning; Li, Qingmei; Wang, Fangyu; Teng, Man; Yang, Yanyan; Deng, Ruiguang; Hu, Xiaofei
Abstract: BACKGROUND: Fumonisins are a kind of toxic and carcinogenic mycotoxin. A rapid immunochromatographic test strip has been developed for simultaneous detection of fumonisin B1, B2 and B3 (FB1, FB2 and FB3 ) in maize based on colloidal gold‐labelled monoclonal antibody (McAb) against FB1 probe. RESULTS: The anti‐FB1 McAb (2E11‐H3) was produced through immunisation and cell fusion, and identified as high affinity, specificity and sensitivity. The cross‐reaction ratios with fumonisin B2 and B3 were accordingly 385% and 72.4%, while none with other analogues. The colloid gold‐labelled anti‐FB1 McAb probe was successfully prepared and used for establishing the immunochromatographic strip. The test strip showed high sensitivity and specificity, the IC50 for FB1 was 58.08 ng mL −1, LOD was 11.24 ng mL −1, calculated from standard curve. Moreover, the test strip exhibited high cross‐reactivity with FB2 and FB3, and could be applied to the simultaneous detection of FBs (FB1 :FB2 :FB3 = 12:4:1) in maize sample with high accuracy and precision. The average recoveries of FBs in maize ranged from 90.42% to 95.29%, and CVs were 1.25–3.77%. The results of the test strip for FBs samples showed good correlation with high‐performance liquid chromatography analysis. CONCLUSION: The immunochromatographic test strip could be employed in the rapid simultaneous detection of FB1, FB2 and FB3 in maize samples on‐site. © 2016 Society of Chemical Industry